KLF7 Regulates Satellite Cell Quiescence in Response to Extracellular Signaling. (28th March 2016) - Wang, Xiaobin; Shen, Qingwu W.; Wang, Jie; Zhang, Zhiguo; Feng, Fu; Chen, Ting; Zhang, Yanyan; Wei, Huan; Li, Zhongwen; Wang, Xinxia; Wang, Yizhen
Abstract: Retaining muscle stem satellite cell (SC) quiescence is important for the maintenance of stem cell population and tissue regeneration. Accumulating evidence supports the model where key extracellular signals play crucial roles in maintaining SC quiescence or activation, however, the intracellular mechanisms that mediate niche signals to control SC behavior are not fully understood. Here, we reported that KLF7 functioned as a key mediator involved in low-level TGF-β signaling and canonical Notch signaling-induced SC quiescence and myoblast arrest. The data obtained showed that KLF7 was upregulated in quiescent SCs and nonproliferating myoblasts. Silence of KLF7 promoted SCs activation and myoblasts proliferation, but overexpression of KLF7 induced myogenic cell arrest. Notably, the expression of KLF7 was regulated by TGF-β and Notch3 signaling. Knockdown of KLF7 diminished low-level TGF-β and canonical Notch signaling-induced SC quiescence. Investigation into the mechanism revealed that KLF7 regulation of SC function was dependent on p21 and acetylation of Lys227 and/or 231 in the DNA binding domain of KLF7. Our study provides new insights into the regulatory network of muscle stem cell quiescence.